Determination of thermophysical characteristics of materials by temperature measurements on the line of a specimen's conjugation with a half-space - Zverev, V. G. (Journal of engineering physics and thermophysics)
Consideration has been given to the coefficient inverse heat conduction problem for determination of thermophysical characteristics of a material by temperature measurements on the line of a specimen's conjugation with a semiinfinite layer of another material with known thermophysical properties. Accounting for heat sink in a thermophysical experiment makes it possible to raise the accuracy of determining the thermophysical characteristics of a material with preservation of its structure and to avoid the need for a laborious effort to ensure the adiabaticity of the specimen's back surface. Based on the analysis of sensitivity coefficients, measurement times have been identified that are the most informative for determining thermophysical characteristics. The proposed methodology removes limitations on the selection of a heating regime for a material and expands a Fourier-number-permissible measurement range.